Anisotropic strengthening of nanotwinned austenitic grains in a nanotwinned stainless steel. (1st January 2018) - Yan, F.K.; Li, Q.; Tao, N.R.
Abstract: Nanotwin lamellae orientation effect on tensile properties of nanotwinned grains strengthening stainless steels was investigated. It is found that the nanotwinned grains with twin lamellae oriented roughly parallel to loading direction exhibit the much higher strengthening effect (at least a GPa higher) than the nanotwinned grains containing twin lamellae inclined to loading direction, which is related to the anisotropic strengthening mechanisms of nanotwins. Graphical abstract: